Analysis of the Effect of Profitability, Company Size, Liquidity, Managerial Ownership, and Audit Opinion on the Timeliness of Submitting Financial Reports - Fatimatus Zehroh; Nur'Aini Rokhmania (Wahana, 2024)
The purpose of this study was to examine the effect of profitability, company size, liquidity, managerial ownership and audit opinion on the timeliness of financial reporting submissions in basic materials sector companies listed on the Indonesia Stock Exchange (IDX). The independent variables in this study are profitability, company size, liquidity, managerial ownership and audit opinion while the dependent variable is the timeliness of financial reporting submissions. The population in this study are companies registered on the IDX for the 2020-2022 period. The sample in this research is additional companies registered on the IDX for the 2020-2022 period in the basic materials sectors. The data collection technique used was purposive sampling, in order to obtain a sample of 62 companies with 169 data that match the criteria. The results of this research show that profitability and liquidity has an effect the timeliness of financial reporting submissions, while company size, managerial ownership and audit opinion has no effect on the timeliness of financial reporting submissions.